Expression and function of endocannabinoid receptors in the human adrenal cortex - Ziegler, C. G. (2010)
Endogenous cannabinoids are important signaling molecules in neuroendocrine control of homeostatic and reproductive functions including stress response and energy metabolism. The hypothalamic paraventricular and supraoptic nuclei have been shown to release endocannabinoids, which act as retrograde messengers to modulate the synaptic release of glutamate during stress response. This study endeavors to elucidate possible interaction of the endocannabinoid system with the regulation of adrenocortical function at the adrenal level. Human adrenocortical NCI-H295R cells and normal human adrenal glands were used to study the possible effects of anandamide and cannabinoid receptor 1 (CB1) antagonist SR141716A on aldosterone and cortisol secretion. Our data indicate the expression of CB1 in human adrenal cortex and adrenocortical NCI-H295R cells; CB2 was not expressed. Furthermore, anandamide inhibited basal release and stimulated release of adrenocortical steroids (corticosterone and aldosterone); this effect was reversed by CB1 antagonist (SR141716A). Therefore, the endocannabinoid system at the level of the adrenal, can directly influence adrenocortical steroidogenesis.